Single-incision robotic cholecystectomy versus single-incision laparoscopic cholecystectomy: A systematic review and meta-analysis. Issue 36 (September 2018) - Sun, Ning; Zhang, Jia Lin; Zhang, Cheng Shuo; Li, Xiao Hang; Shi, Yue
Abstract: Background: Single-incision laparoscopic cholecystectomy (SILC) is the result of the ongoing trend to minimally invasive of laparoscopy, but some surgeons thought that the SILC can increase the risk of bile duct injure or bile spillage, and the single-incision robotic cholecystectomy (SIRC) can overcome the drawbacks of SILC. Some articles described that the SIRC had longer operative time and more cost than SILC. The advantages and disadvantages of SIRC have still not been extensively studied. We aimed to investigate the outcomes of SIRC compared to SILC and evaluate the safety and feasibility of SIRC. Methods: To find relevant studies, the electronic databases PubMed, MEDLINE, The Cochrane Library, and EMBASE were searched to seek information in English literature from 2011 to 2017. Studies comparing SIRC to SILC, for any indication, were included in the analysis. This systematic review and meta-analysis were performed with RevMan Version 5.3. Results: Six comparative studies (n = 633 patients) were included in our analysis. The data showed that the SIRC and SILC had equivalent outcomes for operative time [mean difference (MD) = 17.32, 95% confidence interval (CI): −8.93–43.57, P  = .20], intraoperative complications [odd ratio (OR) = 0.48, 95% CI: 0.17–1.39, P  = .18], postoperative complications (OR = 0.62, 95% CI: 0.21–1.86, P  = .39), hospital stay (MD = −0.01, 95% CI: −0.21–0.19, P  = .90), readmissions rate (OR = 0.70, 95% CI: 0.09−5.63, P  = .74), and conversion rate (OR = 0.52, 95% CI: 0.14–1.96, P  = .33), but total cost was statistically significant (MD = 3.7, 95% CI: 3.61–3.79, P  < .00001). Conclusion: SIRC is a safe and feasible procedure for cholecystectomy, and the operative time is same as SILC, but the total cost of SIRC is significantly higher than SILC.